Efficacy and safety of dexlansoprazole: a comprehensive review - Chaubal, C. C.; Lawate, Parimal; Chaudhury, Sujit; Gupta, Ajay; Shankar, B. Ravi; Pal, Sandip; S., Sharath Kote G.; Patil, Dinesh (International Journal of Research in Medical Sciences, 2023)
Gastroesophageal reflux disease (GERD) remains prevalent in medical practice. Proton pump inhibitors (PPIs) are the primary treatment, yet limitations exist. Dexlansoprazole modified release (MR), an R-enantiomer of lansoprazole, offers high efficacy. Its dual release in the duodenum and small intestine yields two peak concentrations at different times (2- and 5-hours post-administration), ensuring the longest maintenance of drug concentration and proton pump inhibitory effect among all PPIs. Dexlansoprazole MR effectively heals erosive esophagitis, maintains healed esophageal mucosa, and controls NERD symptoms. It also improves nocturnal heartburn, GERD-related sleep disturbances, and bothersome regurgitation. Importantly, it maintains good plasma concentration regardless of food intake, enabling flexible dosing. Furthermore, it does not significantly affect clopidogrel metabolism or platelet inhibition, eliminating the need for dose adjustments when co-prescribed. This review highlights dexlansoprazole’s unique attributes, pharmacokinetics, advantages, and safety in comparison to traditional PPIs.